2021
DOI: 10.1177/2325967121997120
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Lesions of the Distal Tibial Plafond: A Systematic Review of Lesion Locations and Treatment Outcomes

Abstract: Background: Osteochondral lesions of the tibial plafond (OLTPs) remain less common than osteochondral lesions of the talus (OLTs), but recognition of the condition has increased. Purpose: To systematically evaluate the literature on lesion locations and treatment outcomes of OLTPs, whether in isolation or in combination with OLTs. Study Design: Systematic review; Level of evidence, 4. Methods: A search was performed using the PubMed, Embase, and CINAHL databases for studies on lesion locations or with imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Considering previous studies suggesting that additional ankle pathologies such as instability and trauma may affect the incidence, natural history, or treatment outcomes of tibial OCL, 1 we used additional ligament repair surgery as a stratification criterion and tested for homogeneity between the 2 subgroups. Student t test results showed that there were no significant differences in all characteristics between the 2 subgroups ( Table 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering previous studies suggesting that additional ankle pathologies such as instability and trauma may affect the incidence, natural history, or treatment outcomes of tibial OCL, 1 we used additional ligament repair surgery as a stratification criterion and tested for homogeneity between the 2 subgroups. Student t test results showed that there were no significant differences in all characteristics between the 2 subgroups ( Table 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chondral damage of the talus is typically caused by an acute injury, such as a sudden pivot or twist, a fall, or direct blow to the ankle [ 82 ]. Less common causes have been described, such as prolonged immobilization, osteochondritis, alteration in the forces exerted on the articular cartilage, nutritional inadequacies [ 83 , 84 ]. The surgical access (arthroscopy, mini-arthrotomy, arthrotomy) has not been analysed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Areas for future research include the following: the effect of patient factors like body mass index , ethnicity, heredity and theit correlation with the notch of Harty. [6].…”
Section: Discussionmentioning
confidence: 99%